A Gigantic, Exceptionally Complete Titanosaurian Sauropod Dinosaur from Southern Patagonia, Argentina - Lacovara, Kenneth J. (2014)
Titanosaurian sauropod dinosaurs were the most diverse and abundant large-bodied herbivores in the southern continents during the final 30 million years of the Mesozoic Era. Several titanosaur species are regarded as the most massive land-living animals yet discovered; nevertheless, nearly all of these giant titanosaurs are known only from very incomplete fossils, hindering a detailed understanding of their anatomy. Here we describe a new and gigantic titanosaur, Dreadnoughtus schrani, from Upper Cretaceous sediments in southern Patagonia, Argentina. Represented by approximately 70% of the postcranial skeleton, plus craniodental remains, Dreadnoughtus is the most complete giant titanosaur yet discovered, and provides new insight into the morphology and evolutionary history of these colossal animals. Furthermore, despite its estimated mass of about 59.3 metric tons, the bone histology of the Dreadnoughtus type specimen reveals that this individual was still growing at the time of death.